2023
DOI: 10.5194/egusphere-egu23-530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urban water systems as entry points for river plastic pollution

Abstract: <p>Accumulation of plastic in aquatic environments negatively impacts ecosystems and human livelihood. Urban areas are assumed to the main source of plastic pollution in these environments, because of high anthropogenic activity. Yet, the drivers of plastic emissions, abundance and retention within these systems and subsequent transport to river systems is poorly understood. In this study, we demonstrate that urban water systems function as major contributors to river plastic pollution, and explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The mass balance suggests that during the wet season, even more plastic enters the river system from Phnom Penh (Haberstroh et al, 2021a). Also in other urban areas connected to natural river it has been found that during periods of increased rainfall and discharge, more plastic are mobilized and transported into rivers (Tasseron et al, 2022;Treilles et al, 2022). To better quantify and understand sources of riverine plastic, also the seasonality of entry processes should be considered.…”
Section: Changes In the Mass Balancementioning
confidence: 99%
“…The mass balance suggests that during the wet season, even more plastic enters the river system from Phnom Penh (Haberstroh et al, 2021a). Also in other urban areas connected to natural river it has been found that during periods of increased rainfall and discharge, more plastic are mobilized and transported into rivers (Tasseron et al, 2022;Treilles et al, 2022). To better quantify and understand sources of riverine plastic, also the seasonality of entry processes should be considered.…”
Section: Changes In the Mass Balancementioning
confidence: 99%
“…Research on such travel dynamics in urban areas remains scarce. A recent study on Amsterdam found no significant correlations between rainfall and floating plastic transport in either of the six measured canals (Tasseron et al, 2023). For the Huveaune River in Marseille, Tramoy et al (2022) found that 36% of the annual macroplastic transport occurred during heavy rainfall events.…”
Section: Pluvial Floodsmentioning
confidence: 86%
“…Another complicating factor is that plastic pollution comes in countless different polymer types, shapes, rigidity, and sizes, which all influence the way they move through in the environment (van Emmerik & Schwarz, 2020). It is clear that plastic is a purely anthropogenic pollutant, and increased concentrations are generally observed close to densely populated areas (Kuizenga et al, 2023; Tasseron et al, 2023). However, large accumulations are found around the world in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Urban areas, face unique challenges in managing plastic waste due to inadequate infrastructure, informal waste management systems, and socioeconomic disparities. The accumulation of plastic debris in urban waterways, landfills, and coastal areas poses significant ecological and public health risks, necessitating urgent action to mitigate its impact [6], [13]. Plastic waste management in Indonesia is relatively poorly implemented due to the limited number of recyclers, highlighting the need for alternative solutions such as converting plastic waste to paving blocks [14].…”
Section: Plastic Waste Pollution In Urban Areasmentioning
confidence: 99%